Numerical and Experimental Study of the Stern Wedge Effects on the Hydrodynamics Performance of a Semi-Displacement Catamaran in Calm Water - M. Yousefifard; A. Maboodi (Journal of Applied Fluid Mechanics, 2021)
In this article, the calm water resistance and dynamic instabilities of a semi-displacement catamaran fitted with a stern wedge is investigated using an experimental method and numerical technique. This is accomplished in order to probe into the effects of aft geometry modification on semi-displacement ship dynamic characteristics, especially at medium and high speeds. An advanced 6-DOF model that takes into consideration the dynamic mesh method has been utilized in open source code OpenFOAM. Reynolds-Average Navier-Stokes (RANS) equations are solved using standard k-ε turbulence model and VOF method. The accuracy of the current numerical method is investigated by the calm water test in National Persian Gulf Towing Tank. The resistance, trim and sinkage of the ship were monitored during the experiments. The experimental analysis was performed on the initial model and a modified model with 8º wedge at different Froude numbers. After that, the wedges were mounted at different angles at the transom of the vessel and the effect of the angle change for 4 different angles was evaluated using numerical solution. The results show that fitting a stern wedge to this type of ship causes an intense pressure at the stern bottom. Also, it decreases the dynamic trimming and forward resistance of the craft. As well as, stern wedge causes increasing the lift force which affects the reduction of dynamic instabilities. It is concluded that numerical model presented here is quite suitable for accurately predicting dynamic characteristics of a semi-planing twin-hull ships at medium and high Froude numbers. As a result, 14% reduction in total resistance was observed due to the installation of a 6 degree stern wedge.